Wykorzystywanie danych personalnych zgromadzonych przypadkowo podczas operacji bezzałogowych statków powietrznych w świetle standardów prawa do prywatności gwarantowanego w Europejskiej Konwencji o Ochronie Praw Człowieka — zarys problemu - Kociubiński, Jakub (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The rapid growth of data-gathering technologies on the one hand has provided public authorities with a valuable tool for counteracting crimes, but on the other gave rise to concerns over potentially excessive intrusion into persons’ privacy. In order to mitigate the risk of authoritarian behavior stemming from a moral hazard arising out of ability to conduct an ever more eﬀective surveillance, public authorities must impose certain self-limitations with regards to the usage of such data. In this context, the use of unmanned aerial vehicles, which may serve other non-invigilation purposes, may inadvertently lead to collecting someone’s personal data.This paper provides a propaedeutic analysis of legal challenges associated with collateral collection of personal data through unmanned aerial platforms operated by public bodies, and the subsequent use of said data. The analysis will be carried out through the lens of the standards set out in the European Convention on Human Rights (ECHR). In order to provide an answer to the paper’s research question whether the current acquis on Article 8 of the ECHR setting out the basic right to privacy and exceptions thereof require adjustment, the analysis will begin with an overview of the existing case-law dedicated to the ECHR’s standards associated with collecting and processing personal data with an emphasis on its relevance to technical speciﬁ cities of drones operations. The inquiry will then focus on standards associated with operating unmanned platforms during which personal data may be collaterally collected in public places. While it stands to reason that anyone within such a public space must reasonably expect that his or her privacy will be somewhat limited, a distinction must be made between mere recording and the subsequent use of such data for a diﬀerent purpose that it was originally gathered. The next part of the analysis will cover a legal assessment of situations whereby sensors installed on a drone used by public authorities over public spaces will record persons within their domicile — place of living.The analysis carried out in this paper has led to conclusion that while the core of the pre-existing ECHR’s case-law can be successfully applied per analogiam to unmanned aerial platforms’ operations, due to technical and operational factors there is no feasible way to provide adequate information about whether a monitoring is conducted, who is carrying it out, etc., in a similar manner as this is being done in the case of stationary close-circuit cameras. Therefore, it is necessary to place a greater emphasis on ex officio data anonymization.
Keywords: prawo do prywatności; Europejska Konwencja o Ochronie Praw Człowieka; bezzałogowe statki powietrzne; dane osobowe